Konsep Perlindungan Hukum terhadap Konsumen terkait Pembelian Emas berdasarkan Putusan Nomor 1666/Pdt/2022 - Setiawati, Linda (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2024)
Investment developments in society always vary, where one investment instrument with minimal risk is purchasing gold. Gold can be purchased through a state-owned company, namely PT Antam Tbk, with a sales system at its various branch offices. The problem occurs when the branch office sells gold at a discount, which the buyer then agrees to pay first, but the head office rejects this action. This research uses normative juridical research and the results of this research are the legality of buying and selling gold carried out by employees of PT Antam Tb, the transaction is legal if it refers to the provisions of Article 1367 of the Civil Code where the employee who carries out orders and has a core business is liable for losses by the employer, in this case namely PT Antam as the parent company supervises and manages gold as a whole.